SMARCB1/INI1/BAF47‐ deficient pleural malignant mesothelioma with rhabdoid features. Issue 2 (5th January 2018) - Kimura, Noriko; Hasegawa, Masaru; Hiroshima, Kenzo
Abstract : Malignant mesothelioma (MM) with rhabdoid features is an MM variant. Fifteen cases have been reported previously, all of which were combined with other types of MM. Herein, we report an autopsy case of pleural MM with monomorphic rhabdoid features. The patient was a 62‐year‐old male without a history of asbestos exposure. An autopsy revealed a soft, granular tumor that replaced the entire left pleura and had invaded to the diaphragm and lower lobe of the lung. The tumor cells, which had eosinophilic plump cytoplasm and eccentric nuclei, were loosely cohesive. Immunohistochemistry showed that the cells were diffusely positive for calretinin, D2‐40, vimentin, CAM5.2, and AE1/AE3; and negative for WT‐1, TTF‐1, CK7, CEA, desmin, CD34, BCL‐2, S100 protein, and p40. Neither homozygous deletion of p16 nor BAP‐1 protein loss was observed. Loss of INI1/BAF47 protein, an indicator of malignant rhabdoid tumor, was observed. Therefore, MM with rhabdoid features was confirmed.